Magnetic nanoparticles supported copper catalysts: Synthesis of heterocyclic scaffolds. Issue 19 (1st October 2020) - Aqeel Ashraf, Muhammad; Liu, Zhenling; Yang, Yafeng; Zhang, Dangquan
Abstract: Heterocyclic scaffolds are important components in the structure of many drugs and natural products. They are well-known compounds because of their broad spectrum of pharmaceutical and biological activities. In this paper, we provide an overview of the utilization of copper complexes immobilized on magnetic nanoparticles as economical and efficient catalytic systems for the synthesis of heterocyclic molecules. Graphical Abstract: